A Survey of Routing Protocols in Wireless Sensor Networks - Kaur, Navneet; Sahil Verma, Dr.; Kavita, Dr. (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks(WSNs) comprise sensor nodes which find applications in a wide variety of fields such as medical, wildlife, security, environment, industry. A network communication is initialized and accomplished with the aid of routing protocols. A routing protocol is a set of rules which govern the routing phenomenon. WSNs protocols for the purpose of routing have been the ubiquitous option of the researchers in the recent years due to their exorbitant scope of improvement. The objective of a routing protocol is to inquest for a relevant route amidst sender and receiver to accomplish successful transmission at the destination .Dissipation of energy and lengthening the duration of the network have always been one of the major points of research gaps. As the nodes in WSNs in are battery operated, so they can only use restricted energy to proceed with the communication and transmission operation. To cope up with this, a number of researchers have come up with developments in the field of energy efficacy and optimizations in WSNs routing protocols. A reify summarization of some protocols for routing purposes has been manifested in this paper.